2008
DOI: 10.1002/dneu.20657
|View full text |Cite
|
Sign up to set email alerts
|

A subset of signal transduction pathways is required for hippocampal growth cone collapse induced by ephrin‐A5

Abstract: The Eph family tyrosine kinase receptors and their ligands, ephrins, play key roles in a wide variety of physiological and pathological processes including tissue patterning, angiogenesis, bone development, carcinogenesis, axon guidance, and neural plasticity. However, the signaling mechanisms underlying these diverse functions of Eph receptors have not been well understood. In this study, effects of Eph receptor activation on several important signal transduction pathways are examined. In addition, the roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 97 publications
8
25
1
Order By: Relevance
“…Therefore, NO/cGMP/PKG-induced synapse remodeling is dependent on RhoA/ROCK signaling, involving phosphorylation of the ROCK substrate MLC before synapse withdrawal in vitro. This is supported by previous studies showing that cGMP/PKG together with ROCK and/or MLCK mediates growth cone collapse responses to ephrin-B1, ephrin-A5, and semaphorin 3A in cells from different origins [189,190,217]. The function of MLCK is likely to be mediated through MLC phosphorylation, leading to myosin activation and actomyosin contraction [200].…”
Section: In Vitro Evidence From Neonatal Animalssupporting
confidence: 70%
“…Therefore, NO/cGMP/PKG-induced synapse remodeling is dependent on RhoA/ROCK signaling, involving phosphorylation of the ROCK substrate MLC before synapse withdrawal in vitro. This is supported by previous studies showing that cGMP/PKG together with ROCK and/or MLCK mediates growth cone collapse responses to ephrin-B1, ephrin-A5, and semaphorin 3A in cells from different origins [189,190,217]. The function of MLCK is likely to be mediated through MLC phosphorylation, leading to myosin activation and actomyosin contraction [200].…”
Section: In Vitro Evidence From Neonatal Animalssupporting
confidence: 70%
“…antagonism of this repulsion signal was also reported [42] and one study suggested that the outcome may depend on the polarization of the neuronal membrane [59]. PKG1 was also found to act downstream of Ephrin- and Slit- mediated repulsion signals [60], [61] but PKG1 also acted downstream of p53-mediated growth cone extension [42]. It has to be considered that neurite and axon elongation are contributed by shaft stretching [62], which was not specifically addressed and may contribute to the controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Increased RhoA/ROCK activity resulting from long-term action of the NO/cGMP/PKG cascade has been previously suggested in arterial smooth muscle cells (Sauzeau et al, 2003), in the penis (Bivalacqua et al, 2007), and in hearts from diabetic rats (Soliman et al, 2008). In this sense, cGMP/PKG together with ROCK and/or MLC-kinase mediates growth cone collapse responses to ephrin-B1, -A5, and Semaphorin 3A in cells from different origins (Dontchev and Letourneau, 2002;Mann et al, 2003;Yue et al, 2008). The function of MLC-kinase is likely to be mediated through MLC phosphorylation, leading to myosin activation and actomyosin contraction (Luo, 2002).…”
mentioning
confidence: 82%